Evaluating the Implementation and Feasibility of a Web-Based Tool to Support Timely Identification and Care for the Frail Population in Primary Healthcare Settings - Beverley Lawson; Tara Sampalli; Stephanie Wood; Grace Warner; Paige Moorhouse; Rick Gibson; Laurie Mallery; Fred Burge; Lisa G. Bedford (Kerman University of Medical Sciences, 2017)
Background Understanding and addressing the needs of frail persons is an emerging health priority for Nova Scotia and internationally. Primary healthcare (PHC) providers regularly encounter frail persons in their daily clinical work. However, routine identification and measurement of frailty is not standard practice and, in general, there is a lack of awareness about how to identify and respond to frailty. A web-based tool called the Frailty Portal was developed to aid in identifying, screening, and providing care for frail patients in PHC settings. In this study, we will assess the implementation feasibility and impact of the Frailty Portal to: (1) support increased awareness of frailty among providers and patients, (2) identify the degree of frailty within individual patients, and (3) develop and deliver actions to respond to frailtyl in community PHC practice. Methods This study will be approached using a convergent mixed method design where quantitative and qualitative data are collected concurrently, in this case, over a 9-month period, analyzed separately, and then merged to summarize, interpret and produce a more comprehensive understanding of the initiative's feasibility and scalability. Methods will be informed by the 'Implementing the Frailty Portal in Community Primary Care Practice' logic model and questions will be guided by domains and constructs from an implementation science framework, the Consolidated Framework for Implementation Research (CFIR). Discussion The 'Frailty Portal' aims to improve access to, and coordination of, primary care services for persons experiencing frailty. It also aims to increase primary care providers' ability to care for patients in the context of their frailty. Our goal is to help optimize care in the community by helping community providers gain the knowledge they may lack about frailty both in general and in their practice, support improved identification of frailty with the use of screening tools, offer evidence based severity-specific care goals and connect providers with local available community supports.